The plant paradox family cookbook : 80 one-pot recipes to nourish your family using your instant pot, slow cooker, or sheet pan - Gundry, Steven R (Harper Wave, an imprint of HarperCollinsPublishers, 2019)
Since the publication of The Plant Paradox in 2017, hundreds of thousands of people have embraced Dr. Gundry's nutritional protocol--and experienced life-changing results. But most of Dr. Gundry's readers aren't cooking for themselves alone. "How can I extend this way of eating to my entire family? And is it safe for my kids?" are the questions he is most often asked. In The Plant Paradox Family Cookbook, Dr. Gundry reassures parents as he sets the record straight, providing an overview of children's nutritional needs and explaining how we can help our kids thrive on the Plant Paradox program--a diet low in lectins. Dr. Gundry offers shocking evidence of how the Plant Paradox program is not only "safe" for kids, but also the best possible way to set them up for a lifetime of health and responsible eating.